Cesarean Delivery of a Parturient with Lumboperitoneal Shunt under Spinal Anesthesia - Hicham Ziani; Med Yassir Lahbabi; Nabil Elachhab; Nawfel Elcaidi; Aziz Slaoui; Hanaa Lazhar; Sophia Lahbabi; Aziz Baidada; Nezha Oudghiri; Rajae Tachinante (Case Reports in Anesthesiology, 2023)
Lumboperitoneal shunt may be indicated as a treatment for idiopathic intracranial hypertension aiming to facilitate the dynamic flow of cerebrospinal fluid into the peritoneum for patients. Parturients with lumboperitoneal shunt are a few, making it difficult to choose the analgesic or anesthetic technique for delivery. We present the case of a successful spinal anesthesia for a cesarean delivery in a parturient who was diagnosed with idiopathic intracranial hypertension that was treated by lumboperitoneal shunt.